Surfactant-mediated transport behavior of zinc oxide nanoparticles in porous media - Yujue Wang; Zhou Cheng; Ming Wu; Yanru Hao (Ecotoxicology and Environmental Safety)
Nanomaterials and surfactants are widely detected in soil-groundwater environments, while the surfactant-mediated transport behavior of nanoparticles has not been sufficiently investigated. In this study, the transport of ZnO nanoparticles (nZnO) in quartz sand (QS) in the presence of cetyltrimethylammonium bromide (CTAB) is investigated by adsorption and column experiments in combination with XDLVO analysis and numerical simulation. The adsorption of nZnO on QS is investigated by adsorption experiments under the environmental concentration of CTAB (50 mg·L−1). The results of adsorption experiments indicate that the adsorption efficiency of QS is related to the concentration of nZnO and primarily exhibits multilayer adsorption, and the Freundlich model can effectively fit the experimental data of isothermal adsorption. Additionally, the adsorption process is dominated by several factors, among which chemical adsorption is the primary controlling factor. The column experiment results indicate that at higher initial concentrations, the transport capacity of nZnO is weakened due to the occupation of adsorption sites on the QS and the increased collision opportunities between particles. The addition of ionic strength promotes the aggregation of nZnO by reducing electrostatic repulsion, thus inhibiting nZnO transport. Significantly, the inhibition of divalent Ca2+ is stronger than that of monovalent Na+. Interestingly, HA binds mainly to CTAB to form a hydrophobic complex, which reduces the repulsive force between nZnO and QS and inhibits the transport of nZnO. Increasing the pH, nZnO mobility first increases and then decreases, and begins to be inhibited at pH= 9 near the zero-point charge of nZnO. Moreover, at pH= 10, nZnO particles acquire a positive charge due to the adsorption of CTAB, and consequently, they are retained by QS through the hydrophobic interaction between the adsorbed CTABs. In addition, nZnO transport capacity does not increase with CTAB concentration. When a certain concentration of nZnO is reached, nZnO transport capacity is inhibited with CTAB concentration.